When a Friend Becomes Your Enemy: Natural Killer Cells in Atherosclerosis and Atherosclerosis-Associated Risk Factors - Palano, Maria Teresa; Cucchiara, Martina; Gallazzi, Matteo; Riccio, Federica; Mortara, Lorenzo; Gensini, Gian Franco; Spinetti, Gaia; Ambrosio, Giuseppe; Bruno, Antonino (Frontiers in Immunology, 2022)
Atherosclerosis (ATS), the change in structure and function of arteries with associated lesion formation and altered blood flow, is the leading cause of cardiovascular disease, the number one killer worldwide. Beyond dyslipidemia, chronic inflammation, together with aberrant phenotype and function of cells of both the innate and adaptive immune system, are now recognized as relevant contributors to atherosclerosis onset and progression. While the role of macrophages and T cells in atherosclerosis has been addressed in several studies, Natural Killer cells (NKs) represent a poorly explored immune cell type, that deserves attention, due to NKs’ emerging contribution to vascular homeostasis. Furthermore, the possibility to re-polarize the immune system has emerged as a relevant tool to design new therapies, with some succesfull exmples in the field of cancer immunotherapy. Thus, a deeper knowledge of NK cell pathophysiology in the context of atherosclerosis and atherosclerosis-associated risk factors could help developing new preventive and treatment strategies, and decipher the complex scenario/history from “the risk factors for atherosclerosis” Here, we review the current knowledge about NK cell phenotype and activities in atherosclerosis and selected atherosclerosis risk factors, namely type-2 diabetes and obesity, and discuss the related NK-cell oriented environmental signals.